2000
DOI: 10.1063/1.480708
|View full text |Cite
|
Sign up to set email alerts
|

The gas-phase structure of chloroferrocene from microwave spectra

Abstract: Articles you may be interested inRotational spectra of rare isotopic species of fluoroiodomethane: Determination of the equilibrium structure from rotational spectroscopy and quantum-chemical calculations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 12 publications
2
10
0
Order By: Relevance
“…All minima have an eclipsed ring configuration. Though experimentally determined structures are not available for 12 − 14 , a recent gas-phase structure of chloroferrocene reveals an eclipsed conformation (also in agreement with molecular mechanics calculation). In the sense that ferrocenes may be regarded as “three-dimensional arenes”, it may be noted that the gas-phase structures of ethylbenzene and isopropylbenzene have methyl and hydrogen perpendicular and parallel to the ring plane, respectively, 21a,b in contrast to 2 and 13 .…”
Section: Resultssupporting
confidence: 67%
“…All minima have an eclipsed ring configuration. Though experimentally determined structures are not available for 12 − 14 , a recent gas-phase structure of chloroferrocene reveals an eclipsed conformation (also in agreement with molecular mechanics calculation). In the sense that ferrocenes may be regarded as “three-dimensional arenes”, it may be noted that the gas-phase structures of ethylbenzene and isopropylbenzene have methyl and hydrogen perpendicular and parallel to the ring plane, respectively, 21a,b in contrast to 2 and 13 .…”
Section: Resultssupporting
confidence: 67%
“…We first assumed C 2 v symmetry for the vibrationally averaged structure. Second, studies of similar complexes have shown that the cyclopentadienyl rings deviate very little from planarity. Thus, we have constrained the C 5 H 5 rings to be planar in the analysis. Also, the Cp carbon−hydrogen bond distance, r (C−H), was fixed at 1.077 Å, which was the average value from the DFT calculations and was in agreement with the average value from a neutron diffraction study of the (C 5 H 5 ) 2 MoH 2 complex .…”
Section: Discussionmentioning
confidence: 99%
“…However, the monosubstituted derivatives are often difficult to crystalize, and for the 1,1‘-disubstituted derivatives, only one structural isomer has been observed in previous solid-state measurements. In the gas phase, monosubstituted derivatives are readily studied, and multiple conformations of complexes have been observed …”
Section: Introductionmentioning
confidence: 99%